Antifungal Activity of Nanocarriers Containing Tea Tree oil on the Growth of c. Albicans: An Inhibition Profile Study - Flores, Fernanda Cramer (2015)
The aim of this study was to evaluate, for the first time, the antifungal efficacy of nanocapsules suspension and nanoemulsions containing Melaleuca alternifolia essential oil (tea tree oil). Methods and results: An in vitro assay measuring antimicrobial activity against Candida albicans was performed in order to obtain an inhibition profile after 0, 5, 8, 12, 24, 48 and 72 h growth, using two different yeast concentration. The activity of oil-loaded nanostructures on C. albicans growth curve showed differences between formulations. For small concentrations of microorganism, the formulations significantly decreased yeast charge for 48 h. Moreover, the control of growth provided by the nanocapsules remained similar at all analysis times. Conclusions: The inclusion of the oil in nanocapsules proved to be more efficient in reducing and controlling C. albicans growth.